Copper and silver nanowires for CO2 electroreduction. Issue 8 (2nd February 2023) - Conte, Andrea; Baron, Marco; Bonacchi, Sara; Antonello, Sabrina; Aliprandi, Alessandro
Abstract : Copper and silver nanowires as novel electrocatalysts for the electroreduction of CO2 . Abstract : Copper and silver nanowires have been extensively investigated as the next generation of transparent conductive electrodes (TCEs) due to their ability to form percolating networks. Recently, they have been exploited as electrocatalysts for CO2 reduction. In this review, we present the most recent advances in this field summarizing different strategies used for the synthesis and functionalization/activation of copper and silver nanowires, as well as, the state of the art of their electrochemical performance with particular emphasis on the effect of the nanowire morphology. Novel perspectives for the development of highly efficient, selective, and stable electrocatalysts for CO2 reduction arise from the translation of NW-based TCEs in this challenging field.